Modulating effects of bioactive water Naftussya from layers Truskavets’ and Pomyarky on neuro-endocrine-immune complex and metabolism at rats exposed to acute stress - Sydoruk, Nadiya O; Gozhenko, Anatoliy I; Zukow, Walery (Journal of Education, Health and Sport, 2017)
Background. Previously we have been carry out integrated quantitative estimation of neuroendocrine, immune and metabolic responses to acute stress at male and female rats. The aim of this study is to compare the modulating effects of Bioactive Water Naftussya (BAWN) from layers Truskavets’ and Pomyarky on neuro-endocrine-immune complex and metabolism at rats exposed to acute stress. Materials and methods. The experiment is at white rats Wistar line. Rats were divided into intact and 5 test groups treated for seven days with tap (control) water, distilled water as well as table water "Truskavets’ka" and BAWN from Truskavets’ and Pomyarky layers. A day after the end of course animals test groups subjected to water immersion restraint stress. A day after stress determined HRV, endocrine, immune and metabolic parameters as well as gastric mucosa injuries and comparing them with parameters of intact animals. Results. BAWN both Truskavets’ and Pomyarky layers minimizes or obviates abnormal 15 parameters caused by stress, but does not affect the poststressory deviation of 7 parameters. On the other hand, BAWN causes deviation of 15 other parameters which little or do not change under stress. Distilled water and water "Truskavets’ka" affect some parameters the opposite way, other less favorable, but some more favorably than BAWN. Conclusion. BAWN both Truskavets’ and Pomyarky layers limit pathogenic effects of stress, and initiate or enhance its compensatory and sanogenic effects.